TINJAUAN ASPEK KELAYAKAN ELEMEN PEMBENTUK RUANG KOMUNAL DI TAMAN MONUMEN 45 KOTA PEKALONGAN - Setiawan, Moch Fathoni; Purnomo, Andi (Semarang State University, 2016)
Taman Monumen 45 is one of the city park in Pekalongan City, in which there are statues of the heroes as monument to commemorate the services of the heroes. In this park there are also garden element in shape of hard elements and soft elements. Some hard elements are sitting group, pedestrian area, sports area, and the statue of the heroes (sculpture). The hard elements are referred to support the communal activity for the citizens of Pekalongan. They are functioned as for gathering and chatting, lounging, skateboarding and BMX styling. This study aims to assess the feasibility aspects in Taman Monumen 45 in Pekalongan City. From the research, it was revealed that there are some elements of the park that do not meet the eligibility aspect as constituting elements of communal space. It can be seen from the condition of these elements, either hard material or soft material that is still less maintained and is not in accordance with its function.Taman Monumen 45 merupakan salah satu taman kota di Kota Pekalongan yang mana di sana terdapat patung pahlawan sebagai monumenÂ untuk mengenang jasa para pahlawan. Pada taman ini juga terdapat elemen taman berupa elemen keras (hard material) dan elemen lunak (soft material). Elemen keras pada taman ini diantaranya sitting group, area pedestrian, sport area, dan patung pahlawan (sculpture). Elemen keras tersebut sebagai salah satu pendukung aktifitas komunal bagi warga Kota Pekalongan seperti berkumpul, mengobrol dan duduk santai, tempat bermain skateboard dan BMX style. Penelitian ini bertujuan untuk mengkaji aspek kelayakan pada Taman Monumen 45 di Kota Pekalongan. Dari hasil penelitian, terungkap bahwa ada beberapa elemen taman yang tidak memenuhi aspek kelayakan sebagai pembentuk elemen ruang komunal. Hal ini dapat dilihat dari kondisi elemen-elemen tersebut, baik hard material atau soft material yang masih kurang terawat dan tidak sesuai dengan fungsinya.